Prediction of Telkomsel Product Inventory and Sales Using the Fuzzy Time Series (FTS) Method at PT. Graha Informatika Nusantara (GRATIKA) Kisaran - Santoso, Heri; Fakhriza, M.; Manurung, Haidar Azra (STIKOM Tunas Bangsa Pematangsiantar, 2023)
PT. Graha Informatika Nusantara (GRATIKA) is a company engaged in the infocom sector covering the business of Development and Development of Telecommunication Devices and Systems including its support system. Business activities at PT. GRATIKA Coverage includes sales transactions, purchases, and product stock inventory. However, in inventory sales and purchase transactions at PT Graha Informatika Nusantara (GRATIKA) Kisaran, it is difficult to determine how much product inventory to optimize product stock in inventory management and product sales, because there is no prediction system to prevent errors in determining the amount of inventory and product sales. in the future, because the prediction system that is carried out still uses a manual system so it is classified as old and inaccurate. For this reason, a system is needed to predict the inventory and sales of Telkomsel products using the Fuzzy Time Series (FTS) method to facilitate the prediction process so that there are not many errors in the prediction process. This method was chosen because it tends to get a small error value and the process does not require a complex and dynamic learning system of language variables whose linguistic values are fuzzy sets, with the aim of getting maximum profit with the right business strategy plans and techniques. Method This system was developed with the PHP programming language. The results of this study are the application of the FTS method to the system with the Fuzzy calculation process, which results in the prediction of inventory and product sales.